Effectiveness of Cetylpyridinium Chloride in Reducing the Growth of Bacteria that Cause Periodontal Disease - Ernie M. Setiawatie; Rizka Valentina; Rihandhita S. Meiliana (Universitas Sam Ratulangi, 2023)
Abstract: Periodontal disease is a common dental and oral health problem in the community which is usually caused by Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, and Streptococcus mutans. This study aimed to provide information about the cetylpyridinium chloride (CPC) which can inhibit the growth of bacteria that cause periodontal disease. This was a narrative review literature study sourced from Google Scholar, Science Direct, and Pubmed (MEDLINE) databases. The keywords used were CPC inhibition, antimicrobial agent, periodontal pathogen bacteria, periodontal disease, and mouthwash. The results obtained 31 articles with appropriate titles and three review articles. Cetylpyridinium chloride is a mouthwash containing a monocationic quaternary ammonium compound consisting of quaternary nitrogen with a positive charge. with a positive charge. The molecular formula of CPC was C12H38CIN, and the molecular weight was 340g/mol with the IUPAC name 1-hexadecylpyridinium chloride. Cetylpyridinium chloride could inhibit the growth of oral pathogenic bacteria by adsorbing negative charges from bacteria, increasing the permeability of bacterial cell walls, decreasing cell metabolism, damaging cell membranes, and reducing the attachment of bacteria to the tooth surface which could reduce the growth of bacterial cells as the cause of periodontal disease. In conclusion, cetylpyridinium chloride is a potent antibacterial agent suitable used as a mouthwash to prevent periodontal disease. Keywords: cetylpyridinium chloride inhibition; antimicrobial agent; periodontal pathogen bacteria; periodontal disease; mouthwash